ANALISA STRATEGI OPTIMALISASI LIMBAH DALAM UPAYA MENINGKATKAN COMPETITIVE ADVANTAGE DI PT XYZ - Mareza Harlan; Syukri Lukman (Menara Ilmu, 2020)
This study aims to analyze the impact of the waste optimization strategy at PT XYZ during 2013 - 2018. Sources of data used in this study are primary data and secondary data sourced from interviews with company management, Annual Company Reports and data from related units at the company The research results show that during the research period waste optimization provides benefits both financially and non-financially. Financially, the benefits of waste optimization are still fluctuating. This can be caused by several factors such as the limited source of waste material, the limited ability of existing machines, and other factors Keyword: Waste Optimization, Competitive Advantage, Cement Industry